p53 Binds Preferentially to Non-B DNA Structures Formed by the Pyrimidine-Rich Strands of GAA·TTC Trinucleotide Repeats Associated with Friedreich's Ataxia - Helma, Robert; Bažantová, Pavla; Petr, Marek; Adámik, Matej; Renčiuk, Daniel; Tichý, Vlastimil; Pastuchová, Alena; Soldánová, Zuzana; Pečinka, Petr; Bowater, Richard P; Fojta, Miroslav; Brázdová, Marie (Molecules (Basel, Switzerland), 2019)
Expansions of trinucleotide repeats (TNRs) are associated with genetic disorders such as Friedreich's ataxia. The tumor suppressor p53 is a central regulator of cell fate in response to different types of insults. Sequence and structure-selective modes of DNA recognition are among the main attributes of p53 protein. The focus of this work was analysis of the p53 structure-selective recognition of TNRs associated with human neurodegenerative diseases. Here, we studied binding of full length p53 and several deletion variants to TNRs folded into DNA hairpins or loops. We demonstrate that p53 binds to all studied non-B DNA structures, with a preference for non-B DNA structures formed by pyrimidine (Py) rich strands. Using deletion mutants, we determined the C-terminal DNA binding domain of p53 to be crucial for recognition of such non-B DNA structures. We also observed that p53 in vitro prefers binding to the Py-rich strand over the purine (Pu) rich strand in non-B DNA substrates formed by sequence derived from the first intron of the frataxin gene. The binding of p53 to this region was confirmed using chromatin immunoprecipitation in human Friedreich's ataxia fibroblast and adenocarcinoma cells. Altogether these observations provide further evidence that p53 binds to TNRs' non-B DNA structures.
Keywords: Trinucleotide Repeat Expansion; vazba proteinů; expanze trinukleotidových repetic; frataxin; Protein Binding; Friedreichova ataxie; trinucleotide repeat; Humans; Friedreich Ataxia; rekombinantní proteiny; DNA–protein; Gene Expression; lidé; nádorový supresorový protein p53; non-B DNA; interakční proteinové domény a motivy; Trinucleotide Repeats; exprese genu; Protein Interaction Domains and Motifs; konformace nukleové kyseliny; Pyrimidines; p53; Nucleic Acid Conformation; Recombinant Proteins; Tumor Suppressor Protein p53; DNA; DNA hairpin; trinukleotidové repetice; pyrimidiny